2015
DOI: 10.1016/j.hrthm.2015.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Race- and sex-related differences in care for patients newly diagnosed with atrial fibrillation

Abstract: BACKGROUND Atrial fibrillation (AF) is associated with an increased risk of stroke and death. Uniform utilization of appropriate therapies for AF may help reduce those risks. OBJECTIVE We sought to determine whether significant race and sex differences exist in the treatment of newly diagnosed AF in Medicare beneficiaries. METHODS We used administrative encounter data for Medicare beneficiaries to identify patients with newly diagnosed AF during 2010–2011. Services received after initial AF diagnosis were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
90
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(104 citation statements)
references
References 36 publications
11
90
2
1
Order By: Relevance
“…Despite their higher risk of stroke and higher CHADS 2 scores, women were less likely to be on anticoagulation, which may have contributed to increased mortality. Although other studies have documented the lower anticoagulation rates and higher rates of stroke in women with AF in the USA and Canada [11,18,19], no studies have been able to identify the exact cause of this disparity. It has been speculated that older women are more often at risk of falling, which is why they are less likely to be prescribed anticoagulation therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite their higher risk of stroke and higher CHADS 2 scores, women were less likely to be on anticoagulation, which may have contributed to increased mortality. Although other studies have documented the lower anticoagulation rates and higher rates of stroke in women with AF in the USA and Canada [11,18,19], no studies have been able to identify the exact cause of this disparity. It has been speculated that older women are more often at risk of falling, which is why they are less likely to be prescribed anticoagulation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, procedural pursuit of rhythm management in men was evident through the higher rates of electrical cardioversion, AF ablations, and maze surgeries compared to women. A recent study looking at new onset AF in >500,000 Medicare beneficiaries found similar disparities in the treatment of AF by gender with men having higher rates of AF ablations [18]. It is not clear why women are less likely to receive AF ablation since current guidelines recommend AF ablation as a viable first-line treatment option for patients with paroxysmal AF regardless of gender [25].…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9]12,13,14 The underlying reason remains to be determined and may be due to physicians' bias or women's reluctance to undergo an invasive procedure as an early treatment option. In this cohort, fewer women received CA although centers were asked to recruit consecutive patients.…”
Section: Referral Patternsmentioning
confidence: 99%
“…48 Although AF ablation has increased over the past decade, several large administrative registries from Canada and the United States have reported that, in comparison with men, women are substantially less likely to undergo catheter ablation for AF. [49][50][51] Women are older at the time of AF ablation and are referred for the procedure later following presentation than men.…”
Section: Sex Differences In Af Treatment Arrhythmia Managementmentioning
confidence: 99%